Bowel disorders in patients with severe acquired brain injury receiving neurorehabilitation: results from a national survey in Italy - Intiso, Domenico; Montis, Andrea; Scarponi, Federico; Hakiki, Bahia; Cassio, Anna; Lopes, Rossella; Lavezzi, Susanna (Frontiers in Neurology, 2025)
BackgroundSeveral studies have focused the relationship between cerebral lesions and gut function that has been defined as “brain-gut axis.” However, patients with brain damage can also present with different bowel dysfunctions (BDs), frequently observed during rehabilitation stay, such as fecal incontinence, constipation and diarrhea. Limited data has been reported in the literature about the occurrence and management of BDs and no study has yet investigated this issue in patients with severe acquired brain injury (sABI).AimTo investigate basal appraisal regarding BDs issue and therapeutic management in patients with sABI during rehabilitation; interest in examining the issue in depth and improving the knowledge of BDs.DesignCross-sectional.Setting and populationPhysiatrists or neurologists, 99 in total, working in 33 Italian rehabilitation centers involved in the care of sABI giving a pooled sample of 1835 inpatients.MethodOn behalf of the SIMFER a survey questionnaire consisting of 19 close-ended questions with multiple-choice answers and 1 open-ended question was drafted. Items regarded the respondents’ opinions and experiences regarding the epidemiology and management aspects of BDs in patients with sABI. Survey data were collected anonymously via e-mail between July and October 2023.ResultsAll participants knew BDs, but only 18 (40%) and 19 (42.2%) participants were able to provide a definition of diarrhea and constipation, respectively. Eighteen (40%) participants used specific measurements to evaluate BDs. Variable laboratory and instrumental ascertainments were used in diagnosing diarrhea and 84.4% participants requested specialized consultation. All respondents answered that modality and type of nutrition were important in managing BDs. Thirty-six (80%) respondents considered that BDs might increase the incidence of urinary infections and 53.3% answered that BDs might negatively influence the ventricular peritoneal shunt. Participants (95.5%) agreed that mobilization could improve BDs and considered that BDs might hamper recovery (84.4%). The majority showed interest in increasing their knowledge on the topic.ConclusionThe survey detected limited knowledge and uncertainty about epidemiology, definition, and management of BDs in sABI patients, but also interest in exploring and educating oneself on the issue. Future studies should be planned to investigate the burden and the therapeutic strategy to manage BDs.